Knowledge-based Malaysian GLC: Are they more innovative and performing much better? - A. Rahman, Badruddin; Mohd Shariff, Mohd Noor (2008)
Data were collected using a mail survey sent to employees of the listed Government-Linked Companies(GLC). A total of 690 questionnaires were mailed out and 273 were returned and usable, representing a response rate of 39.5%. Using a disproportionately stratified sampling, the data collected was subject to structural equation modelling analysis. The objective is to develop and test a model of knowledge management initiatives, innovation and performance for Malaysian GLC. Confirmatory factor analysis was conducted to examine the validity of the measurement model and the structural model was also analyzed to test the associations hypothesized in the research model. The actual findings showed that the proposed model fits the data well. Employees perceived knowledge management initiatives as important antecedents of innovation, and innovation in turns, result in better organizational performance. The paper is one of the first to find empirical support for the role of knowledge management within GLC.